2006
DOI: 10.2166/wst.2006.854
|View full text |Cite
|
Sign up to set email alerts
|

Examining the influence of substrates and temperature on maximum specific growth rate of denitrifiers

Abstract: Facilities across North America are designing plants to meet stringent limits of technology (LOT) treatment for nitrogen removal (3-5 mg/L total effluent nitrogen). The anoxic capacity requirements for meeting LOT treatment are dependent on the growth rates of the denitrifying organisms. The Blue Plains Advanced Wastewater Treatment Plant (AWTP) is one of many facilities in the Chesapeake Bay region that is evaluating its ability to meet LOT treatment capability. The plant uses methanol as an external carbon s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
26
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 0 publications
9
26
0
Order By: Relevance
“…Acetate can be readily used by other biomasses, but the acetate biomass does not seem to readily use either methanol or ethanol (at least after 24 hours acclimation).CONCLUSIONS † At 138C, the SDNR for methanol grown biomass was found to be approximately 9.2 mg NO 3 -N/g VSS/hr, the SDNR for ethanol grown biomass was about 30.4 mg NO 3 -N/g VSS/hr and the SDNR for acetate utilisers was about 31.7 mg NO 3 -N/g VSS/hr. The denitrification rate with acetate was approximately three times that of methanol confirming other work byMokhayeri et al (2006). † The final (at the end of 24 hour-acclimation) ex situ SDNR value of acetate with ethanol grown biomass was approximately 25.6 mg NO 3 -N/g VSS/hr, and ethanol and acetate with methanol grown biomass was 9.7 and 7.3 mg NO 3 -N/g VSS/hr, indicating near complete acclimation of these substrate-biomass combinations toTable 1 | Comparison of ex situ SDNR rates for the different substrates added to each of the grown biomass during 24 hours SDNR (mg NO 3 -N/g VSS/hr) that of the original substrate-biomass.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Acetate can be readily used by other biomasses, but the acetate biomass does not seem to readily use either methanol or ethanol (at least after 24 hours acclimation).CONCLUSIONS † At 138C, the SDNR for methanol grown biomass was found to be approximately 9.2 mg NO 3 -N/g VSS/hr, the SDNR for ethanol grown biomass was about 30.4 mg NO 3 -N/g VSS/hr and the SDNR for acetate utilisers was about 31.7 mg NO 3 -N/g VSS/hr. The denitrification rate with acetate was approximately three times that of methanol confirming other work byMokhayeri et al (2006). † The final (at the end of 24 hour-acclimation) ex situ SDNR value of acetate with ethanol grown biomass was approximately 25.6 mg NO 3 -N/g VSS/hr, and ethanol and acetate with methanol grown biomass was 9.7 and 7.3 mg NO 3 -N/g VSS/hr, indicating near complete acclimation of these substrate-biomass combinations toTable 1 | Comparison of ex situ SDNR rates for the different substrates added to each of the grown biomass during 24 hours SDNR (mg NO 3 -N/g VSS/hr) that of the original substrate-biomass.…”
supporting
confidence: 86%
“…However, it has been observed that the denitrification process at Blue Plains AWTP is retarded in the winter due to an expected decline in microbial growth rates at lower temperatures. Results from the study conducted at Blue Plains AWTP suggest that the mmax for methanol utilisers at 198C is double the mmax obtained at 138C and denitrification with methanol addition does not achieve low total nitrogen values during the winter (Mokhayeri et al 2006). Minimum winter wastewater temperature at Blue Plains AWTP is approximately 138C.…”
Section: Introductionmentioning
confidence: 95%
“…The maximum specific growth rate using glycerol as the substrate is approximately 2.5 times greater than the μ MAX value of 1.3 d -1 at 20ºC reported by Dold et al (2008) and Nichols et al (2007) using methanol as an external carbon source and similar to the μ MAX values of 3.7 d -1 at 19 ºC for acetate (Mokhayeri et al, 2006). Likely, the μ MAX for glycerol is similar to the μ MAX of acetate.…”
Section: Maximum Specific Growth Rate (µ Max )supporting
confidence: 48%
“…274 heterotrophic bacteria participating in the process (Grabinska-Loniewska et al, 1985;Dold et al, 2008). Methanol is the most widely used external carbon source for denitrification since it is low in cost (Mokhayeri et al 2006). However, the need to evaluate alternate sources of external carbon has been recognized.…”
Section: Introductionmentioning
confidence: 99%
“…Although algal C:N requirements (average of 6.6) are similar to, if not greater than those of denitrifiers (which ranges between 2 and 10), denitrifiers are heterotrophs and so require an organic C source and electron donor to fuel denitrification. Methanol, the most common C compound added to fuel bacteriallymediated denitrification in WRRFs, has many drawbacks including its cost, safety, and reliability [26,49]. By using algae to mediate nutrient removal in bioreactors, the need for organic C additions is removed thereby providing a significant cost savings.…”
Section: Discussionmentioning
confidence: 99%